PENERAPAN QR CODE UNTUK EFISIENSI WAKTU PEMESANAN MENU MAKANAN DAN MINUMAN DI KUSUMA KOPI SEMARANG - Nadia Chairunnisa; Jeffri Alfa Razaq (STEKOM PRESS, 2023)
The coffee shop business is very lively and in great demand some circles of society, wrong one of them is Kusuma Kopi Semarang. Kusuma Kopi Semarang still uses an ordering system that is still manual in terms of ordering, so an ordering system is made menu with the application of a combination of QR Code technology with website. To develop this research, the method used First Come First Served (FCFS). Using this method process Menu ordering is more effective because customers place orders First, you will immediately get service.